PENGARUH SUMBER INFORMASI TERHADAP DENGAN PERAN SUAMI DALAM PENGGUNAAN ALAT KONTRASEPSI IUD PADA PASANGAN USIA SUBUR DI DESA PERCUT KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Laurena Ginting (Jurnal Reproductive Health, 2018)
Intra Uterine Device (IUD) is a highly effective birth control for menjarangkan of pregnancy, the advantage of the wearing of IUD does not affect sexual intercourse, does not affect the quality and the volume of BREAST MILK, can be mounted immediately after childbirth or abort, and fertility return after a quick detachable. IUD contraceptive device selection is influenced by the consent of the spouses, the education, knowledge, economic, cultural influence acceptors in choosing birth control IUD, the most dominant influence is a factor of IUD acceptors chose education. Education affect a prospective acceptors to choose the contraceptive method that is used. As for the goal in this research is to know the influence of information resources with the role of the husband in the use of contraceptives IUD on fertile age couples in the village of Percut Sei Tuan Subdistrict Percut Deli Serdang district the year 2018. This research uses qualitative and quantitative design. This type of research kuatitatif is a survey with cross sectional survey approach. This research was conducted in the village of Percut Sei Tuan Subdistrict Percut Deli Serdang district. The selection of the location due to the high Fertile Age Couples (PUSSY) the number of IUD contraceptive usage and sufficient for researched and have never done research on the influence of the role of the husband towards women in fertile age couples using contraceptives IUD. Data analysis in this research by using the Chi-Square test with ÃŽÂ± = 0.05. The chi square test results obtained the value of p = 0,201 > 0.05, thus there is no relationship between information sources with the role of education. The results showed the husband's role as a motivator. Based on interviews in the field that the women of fertile age in couples using contraceptives IUD expressed support the husband use birth control IUD by reason of birth control IUD is easy, secure, menjarangkan pregnancy, prevent pregnancy, most suitable, appropriate, long-term birth control and economic problems. However, there is also the husband of the wife was not in favor of using IUD on the grounds of the decision, which had the wife the husband did not know about the KB, and because hisown wife's wishes